109k views
0 votes
Simplify: cos2x+cos4 all over sin2x - sin 4x

Simplify: cos2x+cos4 all over sin2x - sin 4x-example-1
User Bixms
by
4.3k points

2 Answers

0 votes

1400 answer choice B

User Mohammad Mirsafaei
by
4.9k points
1 vote

Answer:


(\cos\left(2x\right)+\cos\left(4x\right))/(\sin\left(2x\right)-\sin\left(4x\right))=-\cot\left(x\right)

Explanation:


(\cos\left(2x\right)+\cos\left(4x\right))/(\sin\left(2x\right)-\sin\left(4x\right))

Apply formula:


\cos\left(A\right)+\cos\left(B\right)=2\cdot\cos\left((A+B)/(2)\right)\cdot\cos\left((A-B)/(2)\right) and


\sin\left(A\right)-\sin\left(B\right)=2\cdot\cos\left((A+B)/(2)\right)\cdot\sin\left((A-B)/(2)\right)

We get:


=(2\cdot\cos\left((2x+4x)/(2)\right)\cdot\cos\left((2x-4x)/(2)\right))/(2\cdot\cos\left((2x+4x)/(2)\right)\cdot\sin\left((2x-4x)/(2)\right))


=(\cos\left((2x-4x)/(2)\right))/(\sin\left((2x-4x)/(2)\right))


=(\cos\left((-2x)/(2)\right))/(\sin\left(-(2x)/(2)\right))


=(\cos\left(-x\right))/(\sin\left(-x\right))


=(\cos\left(x\right))/(-\sin\left(x\right))


=-\cot\left(x\right)

Hence final answer is


(\cos\left(2x\right)+\cos\left(4x\right))/(\sin\left(2x\right)-\sin\left(4x\right))=-\cot\left(x\right)

User Letoncse
by
5.0k points